Relational marketing strategy of LAZISNU to strengthen muzakki trust - Masrur, Muhamad; Misdawati, Dwi Novaria; Ahmad, Umar Ali; Lawal, Uthman Shehu; Andrean, Rizky (Review of Islamic Social Finance and Entrepreneurship, 2026)
Purpose – This study aims to analyze the relational marketing strategy of the Nahdlatul Ulama Amil Zakat, Infaq, and Sadaqah Institution (Lembaga Amil Zakat, Infak, dan Sedekah Nahdlatul Ulama, LAZISNU) Institute in strengthening muzakki trust in Central Java. The primary focus is on how communication, service quality, transparency, and sociocultural factors contribute to the formation of trust and loyalty among muzakki. Methodology – This research employs a descriptive qualitative approach and utilizes in-depth interviews, observations, and document analysis at several LAZISNU branches in Central Java. Thematic analysis techniques were used to identify the patterns of relationships and dynamics of muzakki beliefs. Findings – The research results show that personal communication, responsive service, and transparent reporting are the primary pillars of strengthening muzakki trust. Nahdliyin’s socio-cultural network’s support accelerates the adoption of relational strategies and increases donation loyalty. Community-based strategies have been proven to create emotional closeness, a sense of belonging, and the sustainability of donations. Implications – Relational strategies reduce digital trust deficits through transparent digital reporting, personalized communication, CRM-based donor tracking, and participatory program monitoring that verifies real social impact. Originality – This research integrates a relational marketing perspective with NU’s sociocultural studies to develop a new model for understanding the formation of muzakki trust in community-based Islamic philanthropic institutions.